Asset inflation and monetary policy - Charles P. Kindleberger (PSL Quarterly Review, 2009)
Asset inflation is characterised by an increase in the prices of assets while output prices are relatively stable or on a decline. In the event of asset inflation, international coordination of monetary policy is an observable trend. For instance, in 1989, when Japan was at the worst phase of the recession, the Bank of Japan lowered interest rates and the US and German discount rates also declined at the same time. However, most mainstream economists believe that monetary policy should be aimed at the stability of the general price level rather than zeroing on asset prices. The nature, importance and historical evolutionary of concern with asset inflation are discussed. Paper originally published in the BNL Quarterly Review, vol. 48 n. 192, March, 1995 pp. 17-37.